Serum Albumin and Circulating Metabolites and Risk of Venous Thromboembolism: A Two-Sample Mendelian Randomization Study - Liu, Zhengye; Mi, Jiarui (Frontiers in Nutrition, 2021)
Background and Aim: Previous observational studies indicated that the serum albumin levels and circulating metabolites are associated with a high risk of venous thromboembolism (VTE). However, whether these observations reflect causality remained unclear. Hence, we conducted a two-sample Mendelian randomization (MR) analysis to evaluate the causal associations of serum albumin and circulating metabolites with the risk of VTE. Methods and Results: Summary statistics of genetic instruments proxying serum albumin, total protein, and common circulating metabolites were extracted from genome-wide association studies in the European ancestry. Summary-level results of age- and sex-adjusted estimates for associations of the instruments with VTE were derived from the FinnGen consortium. We used the inverse-variance weighted (IVW) method as the primary analysis for univariable MR. Sensitivity analyses were performed to detect horizontal pleiotropy and outliers. Genetically proxied high-serum albumin and total protein levels were suggestive protective factor of VTE, with odds ratio (OR) = 0.69 (CI 0.54–0.89, p = 4.7 × 10−3) and 0.76 (CI 0.61–0.95, p = 0.015), respectively. Genetically proxied low-monounsaturated fatty acids and the ratio of monounsaturated fatty acid to total fatty acid are causally associated with increased risk of VTE, with ORs = 0.89 (CI 0.80–0.99, p = 0.031) and 0.85 (CI 0.78–0.94, p = 9.92 × 10−4), respectively. There is no indication of causal associations between other circulating metabolites and the risk of VTE. Conclusions: Genetically liability to low-serum albumin and total protein levels, low proxied monounsaturated fatty acids (MUFAs) and the ratio of MUFAs to total fatty acids are associated with the higher risk of VTE.